Testweights and Protein Content In Bajra In Relation To Methods of Sowing, Mnaurial Treatments and Seed Rates - Tomar, P S (Annals of Arid Zone, 2016)
Under broadcast sowing, the test weight and protein content in Pennisetum typhoides improved appreciably over that under line sowing. Application of 55 Kg N/ha at sowing, half as ammonium sulphate plus half as compost gave the highest test weight and maximum contents of protein in grain and stover. 2.5 Kg seed rate gave significantly heavier testweight and nonsignificantIy greater protein content in grain and stover.